Behavioural roots and system effects of residential electric heating DSM - Dahlman, Yrsa; Gerhardsson, Hanna (My University, 2017)
In a wind dominated future electricity system, consequences of intermittency can be reduced through residential demand side management (DSM), but studies on this subject generally lack understanding of resident behaviour. This work is an interdisciplinary master's thesis, aiming to bridge the gap between behavioural studies and electricity systems modelling. The work is carried out at the Department of Energy and Environment at Chalmers University of Technology, in cooperation with the research group of Environmental Psychology at Gothenburg University, and relates to previous electricity system research on DSM of electric heating in Swedish single family dwellings (SFDs) in a future scenario of a north European wind dominated electricity system. A survey is sent out and answered by 338 E.ON customers living in SFDs. The survey answers are used to model the potential for Swedish electric heated SFDs to reduce costs and emissions in a wind dominated northern European electricity system by accepting variations in their indoor temperatures. The outcome shows that there is potential to reduce electricity demand by around 1.6TWh/year, costs by around 120M€ and (0 2 emissions by around 870 tonnes by applying DSM in all Swedish SFDs with electric heating. If it is desired to stimulate additional DSM efforts in SFDs it is found that system benefits are larger when making the household's accept a slight increase in variations all time, rather than allowing for a significant increase in temperature variations at times when no one is home. It is found that people are overall willing to participate in the DSM-scheme and that they are mainly motivated by the environmental benefits, regarding DSM as mitigating the social dilemma of climate change. The main factor explaining the participation level is found to be the respondents awareness of the connection between electricity use and climate change. Further research is suggested for residential DSM in other system contexts, such as countries without hydropower which can be expected to be more affected by wind intermittency. Future pilot studies investigating actual, rather than theoretical, household participation and experiences of temperature variations are also suggested.
Keywords: Energi; Hållbar utveckling; Energiteknik; Energy; Sustainable Development; Energy Engineering